Influence of Psychological Intervention on Children with Learning Disability - Jiang, Qixuan (Transactions on Social Science, Education and Humanities Research, 2024)
At present, Children with learning disability are increasingly exposed to the social landscape. Their situation has caused widespread public concern, as a treatment for learning disability, psychological intervention for children with learning disability has become one of the hot issues of social debate. To examine the influence of psychological intervention on children with learning disability, researchers have done relevant studies and thrown out different opinions. Therefore, by collecting research reports from different researchers and analyzing the data, this paper explores the influence of psychological intervention on children with learning disability. Through statstics, studies have found that psychological intervention can improve the academic performance of children with learning disability at school, their grades have improved a lot and they are more active in class. It can also reduce the unhealthy emotions of children with learning disability, so that children with learning disability can become more confident and more positive, as well as better integrate into society. Based on the conclusion, it is suggested that different individuals should raise their awareness, increase attention for children with learning disability that still exist and then bring to bear on some psychological interventions.